Data-Driven Web-Based Service Travel Resume Information System - Marlindawati, .; Misinem, .; Andini Sidqin, Maza (INTI International University, 2024)
The Energy and Mineral Resources Department (ESDM) of South Sumatra Province has significantly enhanced its operational efficiency by implementinga Web-Based Official Travel Resume Information System. This system was developed to address the inefficiencies and risks associated with the previous manual method of managing official travel data. The new system leverages PHP, MySQL, Javascript, JQuery, and Bootstrap to provide a robust, secure, and user-friendly platform for handling travel reports, assignment orders, and official travel documentation. The digital transformation has streamlined data entry, improved data integrity, and facilitated real-time information access,enabling better decision-making and strategic planning. A System Usability Scale (SUS) test was conducted with 120 participants to evaluate the system's usability. The results showed a mean SUS score of 78.5, indicating good usability, with a standard deviation of 8.3. High scores were recorded for the system's ease of use, integration of functions, and user confidence, while lower scores highlighted initial complexity and a need for additional user training. The successful implementation and positive usability results underscore the system's effectiveness in enhancing the ESDM Department's operational capabilities. Recommendations for further improvements include enhancing mobile accessibility, providing ongoing user training, integrating advanced reporting features, and refining the user interface to ensure continued user satisfaction and system efficiency.